Requirements Engineering: Foundation for Software Quality 14th International Working Conference, REFSQ 2008 Montpellier, France, june 16-17, 2008, Proceedings - Paech, Barbara.; Paech, Barbara.; Rolland, Colette.; Rolland, Colette. (Programming and Software Engineering, 2008)
This book constitutes the refereed proceedings of the 14th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2008, held in Montpellier, France, in June 2008. The 17 revised full papers presented together with an introduction of the editors and the keynote lecture were carefully reviewed and selected from 50 submissions. The papers are organized in thematic sections on fitness of RE, requirements elicitation, industrial experience of RE, innovative systems, maturing research, and empirical studies.